RyR-ing up nuclear calcium signaling and CREB-mediated gene expression. (December 2021) - Jeziorek, Maciej; Dobrowolski, Radek
Highlights: In a recent study Lobos et al., 2021 [6] show that RyRs and specifically RyR2, the predominant form of this receptor in rat hippocampal neurons, not only amplify calcium levels but strongly contribute to a generation of a nuclear calcium signal. The authors show that an inhibition of RyR-mediated calcium release using ryanodine (Rya) or by depleting RyR2 expression using RNAi blunted nuclear calcium levels in cultured rat neurons by approximately 50-75%. Graphical abstract: Image, graphical abstract